Bacteriophage Mediates Efficient Gene Transfer in Combination with Conventional Transfection Reagents - Donnelly, Amanda (Viruses, 2015)
The development of commercially available transfection reagents for gene transfer applications has revolutionized the field of molecular biology and scientific research. However, the challenge remains in ensuring that they are efficient, safe, reproducible and cost effective. Bacteriophage (phage)-based viral vectors have the potential to be utilized for general gene transfer applications within research and industry. Yet, they require adaptations in order to enable them to efficiently enter cells and overcome mammalian cellular barriers, as they infect bacteria only; furthermore, limited progress has been made at increasing their efficiency. The production of a novel hybrid nanocomplex system consisting of two different nanomaterial systems, phage vectors and conventional transfection reagents, could overcome these limitations. Here we demonstrate that the combination of cationic lipids, cationic polymers or calcium phosphate with M13 bacteriophage-derived vectors, engineered to carry a mammalian transgene cassette, resulted in increased cellular attachment, entry and improved transgene expression in human cells. Moreover, addition of a targeting ligand into the nanocomplex system, through genetic engineering of the phage capsid further increased gene expression and was effective in a stable cell line generation application. Overall, this new hybrid nanocomplex system (i) provides enhanced phage-mediated gene transfer; (ii) is applicable for laboratory transfection processes and (iii) shows promise within industry for large-scale gene transfer applications.